Research on the Concepts of Employability and Competencies as a Driver of Educational Change through a Bibliometric Study - Cortejoso Lino, María; Bartolomé Muñoz de Luna, Ángel; Martín Gómez, Sonia (Street Art & Urban Creativity, 2025)
Two decades ago, the member states of the European Union initiated a reform of university education with the aim of promoting employability, emphasising the importance of soft skills beyond the specific techniques of each degree. However, a significant discrepancy persists between the demand for these skills by the labour market and the supply by universities. This study employs a bibliometric analysis of scientific publications in the Web of Science and Scopus databases during the period 1996-2022 to analyse the impact of employability and soft skills on the scientific community. The study’s primary findings indicate an increase in scientific production from 2010 onwards, accompanied by a notable absence of scientific collaboration, with 90% of papers being signed by a single author. The United Kingdom and Australia are observed to be performing significantly better than Spain in these aspects, with an 80% increase in scientific output.